2013
DOI: 10.1136/bmj.f228
|View full text |Cite
|
Sign up to set email alerts
|

Long term calcium intake and rates of all cause and cardiovascular mortality: community based prospective longitudinal cohort study

Abstract: Objective To investigate the association between long term intake of dietary and supplemental calcium and death from all causes and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
172
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 61 publications
11
172
2
9
Order By: Relevance
“…24,25 A more recent study showed that calcium supplementation improves short-term outcomes in intensive care unit patients with hypocalcemia. 26 Thus, further investigations are needed to determine whether calcium-supplementation therapy in ACS patients with low serum calcium could improve their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 A more recent study showed that calcium supplementation improves short-term outcomes in intensive care unit patients with hypocalcemia. 26 Thus, further investigations are needed to determine whether calcium-supplementation therapy in ACS patients with low serum calcium could improve their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the long-term consumption patterns of diets containing total calcium amounts greater than 1400 mg per day from foods and supplements, women (not men) are at increased risk of death from all causes, including cardiovascular disease with the exception of stroke [14]. Further investigation of this important relationship is needed, but the suggestion that more calcium, especially from supplements, is better for bone health and possibly other aspects of health is not supported by recent evidence.…”
Section: Calcium Intake and Mortality From All Causesmentioning
confidence: 76%
“…Según el IOM, la ingesta máxima admisible de calcio no debe superar los 2.500mg/persona/día 5 . En un estudio sobre una cohorte prospectiva de 61.433 mujeres nacidas entre el 1914 y el 1948 de la Swedish mammography cohort 28 , seguidas durante 19 años, se estimó que una ingesta alta de calcio diario por encima de las recomendaciones (mayor de 1.400mg/día) proveniente tanto de la dieta como de suplementos se asociaba con mayor mortalidad media por cualquier causa y por causa cardiovascular, cuando se comparaba con aquellas que realizaban una ingestión entre 600-1.000mg, rango de ingesta que correspondería a un 35% de la población presentada en este estudio.…”
Section: Discussionunclassified